2014
DOI: 10.1111/aor.12269
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Array of Microfluidic Oxygenators as a Neonatal Lung Assist Device: In Vitro Characterization and In Vivo Demonstration

Abstract: A miniaturized oxygenator device that is perfused like an artificial placenta via the umbilical vessels may have significant potential to save the lives of newborns with respiratory insufficiency. Recently we presented the concept of an integrated modular lung assist device (LAD) that consists of stacked microfluidic single oxygenator units (SOUs) and demonstrated the technical details and operation of SOU prototypes. In this article, we present a LAD prototype that is designed to accommodate the different nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(91 citation statements)
references
References 33 publications
1
82
0
Order By: Relevance
“…As the evolution of extracorporeal membrane oxygenation continues, it is becoming possible to overcome past limitations of blood‐side resistance to gas exchange. PDMS thin films can be produced at less than 20 μm thickness and greatly surpass the low permeability of early polymer membranes , and modern fabrication techniques can reliably produce defect‐free membranes that minimize the risk of gas embolism . The stacked parallel plate blood channels used in the first clinical membrane oxygenators can now be reproduced using soft lithography to yield sub‐10 μm channel heights , significantly reducing plasma boundary layers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the evolution of extracorporeal membrane oxygenation continues, it is becoming possible to overcome past limitations of blood‐side resistance to gas exchange. PDMS thin films can be produced at less than 20 μm thickness and greatly surpass the low permeability of early polymer membranes , and modern fabrication techniques can reliably produce defect‐free membranes that minimize the risk of gas embolism . The stacked parallel plate blood channels used in the first clinical membrane oxygenators can now be reproduced using soft lithography to yield sub‐10 μm channel heights , significantly reducing plasma boundary layers.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, Rochow et al used PDMS to define the blood channels, testing both 6 μm thick microporous polycarbonate membranes or 20 μm thick PDMS for gas exchange. This enabled blood channels with 80 μm height and 500 μm width in a stackable design . The high gas permeability of the thin PDMS membranes enabled the use of ambient air as a sweep gas, which could make dedicated pure oxygen supplies and gas mixers unnecessary.…”
Section: Microfluidics Mimic Native Lungs: 1990s–futurementioning
confidence: 99%
“…24–25 Most reports of microfluidic oxygenators have been limited to blood flow rates of 5 mL/min or less; 17, 18, 21, 2629 one has reported blood flow rates as high as 40 mL/min, but the oxygen content of the blood appeared to drop below commercial oxygenator oxygen transfer levels (5 volume percent oxygen relative to the total blood volume) above 10 mL/min blood flow rates. 30 Another recent report from Rieper et al has demonstrated blood oxygen transfer at blood flow rates as high as 60 mL/min, clearly a major advance over most of the microfluidic literature [T. Rieper, C. Muller and H. Reinecke, However, this report does not describe an approach to ensure that blood flow patterns in the channel structures are designed in a manner to avoid sharp corners and non-physiologic and potentially deleterious flow paths. This highlights the need to develop strategies for larger scale devices while retaining the advantages of microfluidic devices in achieving and maintaining blood stability in the flow networks.…”
Section: Resultsmentioning
confidence: 99%
“…However, its application was limited by the risk of intraventricular hemorrhage that may follow full body anticoagulation, which is usually required in extracorporeal oxygenation. 84 One method to improve hematocompatibility and prevent clotting is the use of ECs. 81 The study provides new ideas and foundations for the development of cell-based organ-on-a-chip systems in a similar way, whether as a respiratory assist device or in other organ optimization device, a concept proposed in the present article.…”
Section: Multi-organ-on-a-chip Platformsmentioning
confidence: 99%